Development of mortgage lending and issues of methodology for determining the housing affordability - A. L. Belousov (Russian Journal of Economics and Law)
Objective: to study the development of mortgage lending in the Russian Federation from 2000 to 2017 and to assess its impact on the indicators of housing affordability for the population.Methods: analysis, synthesis, systemic approach, formal legal method.Results: the author identifies the main criteria of housing affordability, which are currently used in practice. The emphasis is made on the coefficient of housing affordability set at the legislative level. With the help of generalized data, the dynamics of this coefficient is analyzed in terms of introducing the mortgage lending mechanisms into practice. It is concluded that mortgage per se does not make housing more affordable. In the short term, on the contrary, by increasing effective demand, mortgage loans raise prices for residential real estate. Only in the medium and long term, the development of mortgages, with proper regulation, can increase availability of housing for the population through stimulating the construction sector, where capital investment is due to the growth of solvent demand, and through increasing the amount of new residential real estates built annually. Scientific novelty: the author identifies shortcomings of the method of determining the housing affordability coefficient, contained in the legislation, as it does not take into account the current expenditures of households. It is proposed to adjust this indicator to the subsistence level for each family member. The calculation on the modified model is carried out. It is proposed to apply a simpler and more objective indicator of housing affordability for the population, which is the ratio of income to the cost of a square meter of residential real estate.Practical significance: the assessment of the impact of mortgage lending development on the level of housing affordability obtained in the work has a high degree of relevance in terms of further regulating mortgage as a banking product, as well as selecting the direction of development of state policy in the field of residential construction.